Systematic investigation of the emerging pathogen of Tsukamurella species in a Chinese tertiary teaching hospital - Shuying Yu; Xiaoqi Ding; Kexin Hua; Huiqing Zhu; Qingshui Zhang; Xinuo Song; Xiuli Xie; Rong Huang; Yingchun Xu; Li Zhang; Qiaolian Yi; Ying Zhao (Microbiology Spectrum, 2023)
ABSTRACT Tsukamurella species have been clinically regarded as rare but emerging opportunistic pathogens causing various infections in humans. Tsukamurella pneumonia has often been misdiagnosed as pulmonary tuberculosis due to its clinical presentation resembling tuberculosis-like syndromes. Tsukamurella species have also been confused in the laboratory with other phylogenetic bacteria, such as Gordonia. This study aimed to investigate the clinical, microbiological, and molecular characteristics; species distribution; and antimicrobial susceptibility of Tsukamurella species. Immunodeficiency and chronic pulmonary disease appeared to be risk factors for Tsukamurella pneumonia, and the presence of bronchiectasis and pulmonary nodules on imaging was highly correlated with this infection. The study confirmed that groEL (heat shock protein 60) and secA (the secretion ATPase) genes are reliable for identifying Tsukamurella species. Additionally, the ssrA (stable small RNA) gene showed promise as a tool for discriminating between different Tsukamurella species with the shortest sequence length. In terms of antimicrobial susceptibility, quinolones, trimethoprim/sulfamethoxazole, amikacin, minocycline, linezolid, and tigecycline demonstrated potent in vitro activity against Tsukamurella isolates in our study. The study also proposed a resistance mechanism involving a substitution (S91R) within the quinolone-resistance-determining region of the gyrA gene, which confers resistance to levofloxacin and ciprofloxacin. Furthermore, we found that disk diffusion testing is not suitable for testing the susceptibilities of Tsukamurella isolates to ciprofloxacin, imipenem, and minocycline. In conclusion, our systematic investigation may contribute to a better understanding of this rare pathogen. Tsukamurella species are rare but emerging human pathogens that share remarkable similarities with other mycolic acid–containing genera of the order Actinomycetales, especially Mycobacterium tuberculosis. Consequently, misdiagnosis and therapeutic failures can occur in clinical settings. Despite the significance of accurate identification, antimicrobial susceptibility, and understanding the resistance mechanism of this important genus, our knowledge in these areas remains fragmentary and incomplete. In this study, we aimed to address these gaps by investigating promising identification methods, the antimicrobial susceptibility patterns, and a novel quinolone resistance mechanism in Tsukamurella species, utilizing a collection of clinical isolates. The findings of our study will contribute to improve diagnosis and successful management of infections caused by Tsukamurella species, as well as establishing well-defined performance and interpretive criteria for antimicrobial susceptibility testing.